Sri Lanka : 2013 Article IV Consultation and Proposal for Post-Program Monitoring. (IMF Staff Country Reports; Country Report ;, 2013)
The paper discusses the economic developments and policies in Sri Lanka in recent years. Substantial adjustments in energy prices and operational and financial reforms have helped to improve the performance of state owned enterprises (SOEs) and have reduced the burden on the budget and the banking system. Despite challenging global and domestic market conditions, overall soundness of the financial sector has improved with higher levels of capital, liquidity, and healthy earnings. The Sri Lankan economy is expected to return to a high growth trajectory, though conditional on recovery in external demand.